Keaksaraan Fungsional Berbasis Wirausaha Produktif Untuk Kemandirian Masyarakat - Rudi Amir (Universitas Negeri Makassar, 2018)
This study uses a qualitative approach, with this type of research is a case study research by collecting data that is qualitative. This study aims to determine: 1) How big the contribution of functional literacy programs based on productive entrepreneurs in improving community independence in Je'netallasa Village Pallangga District Gowa Regency; The subjects of the study were the citizens of functional literacy learning based on productive entrepreneurs in Jenetallasa Village, Pallangga District, gowa district, as many as 5 people. The results showed that: 1) Learning functional literacy in Je'netallasa Village Pallangga District Gowa District gave positive results to the community. The perceived result is that mothers who previously could not read and write can now be said to be free from illiteracy problems, they began to have calistung ability as an effort to eradicate illiteracy society; 2) The functional literacy capabilities and productive entrepreneurial skills of the respondents, in the form of knowledge about reading, writing and numeracy (calistung). While in the form of skills, obtained through learning practices, among others: making bosara from plastic drink glass and syrup made from cucumber suri. 3) Factors that play a role in supporting respondents in managing their. business in the field of sewing are: capital knowledge and skills, motivation for independence, adequate literacy, age conditions. Some things inhibiting the respondents in managing business in the field of sewing business, among others: lack of capital, marketing efforts are still lacking